Community pharmacists' opinions of their role in administering non-prescription medicines in an emergency - McMillan, S.; Hattingh, Laetitia; King, M. (Springer Science + Business Media, 2011)
Objective: To obtain community pharmacists’ opinions of their role in administering Pharmacy (S2) and Pharmacist Only (S3) Medicines in a medical emergency. These medicines can only be sold in a pharmacy and are not available for self-selection by patients. Whilst qualified pharmacy assistants can supply S2 medicines, pharmacists must be directly involved in the supply of S3 medicines. Setting: Community pharmacies in South East Queensland, Australia. Method: A survey of 151 Gold Coast and Toowoomba community pharmacists was conducted during October 2009. Main outcome measures: Pharmacists were asked their opinions as to whether the administration of S2 and S3 medicines should fall within their scope of practice, whether they had administered S2 and S3 medicines in a medical emergency in the past and if clarification of this role was required. Results: The study achieved a 30% (n = 45) response rate and demonstrated similar results regarding whether pharmacists should administer salbutamol (22/44), adrenaline (23/42), glyceryl trinitrate (22/43) and aspirin (18/36) in a medical emergency. The majority (36/43) believed that role clarification was required. Pharmacists were more likely to administer an S3 medicine in a medical emergency when they considered potential outcomes first, had no easy access to a doctor and the patient could not administer the medicine they carried with them themselves (40/45).Conclusion: Community pharmacists have direct access to S2 and S3 medicines that could be required in the management of a variety of medical emergencies. This study demonstrates that some pharmacists have administered S2 and S3 medicines in an emergency situation. However, there are currently no clear guidelines for pharmacists when faced with a medical emergency other than to act within their professional competence. To promote patient safety through the appropriate use of S2 and S3 medicines in the event of a medical emergency, additional training of pharmacists on the administration of these readily accessible medicines is needed. Clarification of the role of pharmacists in an emergency situation is required.